Radioprotective action of extracellular adenosine on bone marrow cells in mice exposed to gamma rays as assayed by the micronucleus test - Hofer, M; Mazur, L; Pospísil, M; Weiterová, L; Znojil, V (Radiation research, 2000)
The frequency of micronucleated polychromatic erythrocytes (PCEs) in mouse bone marrow was assessed after administration of dipyridamole and/or adenosine monophosphate (AMP) to nonirradiated mice or to mice irradiated 15 min later with a sublethal dose of 6.5 Gy gamma rays. In nonirradiated mice, the administration of the drugs increased the frequency of micronucleated PCEs significantly (by 108%). In contrast, in irradiated mice, the number of radiation-induced micronucleated PCEs was significantly decreased if the mice had been pretreated with dipyridamole or AMP alone (by 24% after administration of each of the compounds) and in particular after administration of the drugs in combination (by 36%).
Keywords: DNA Damage; adenosinmonofosfát; Radiation-Protective Agents; inhibitory fosfodiesteras; Male; Micronucleus Tests; mikrojaderné testy; poškození DNA; mužské pohlaví; Mice; Phosphodiesterase Inhibitors; záření gama; Mice, Inbred Strains; inbrední kmeny myší; Drug Combinations; buňky kostní dřeně; fixní kombinace léků; Adenosine Monophosphate; Erythrocytes; zvířata; erytrocyty; Bone Marrow Cells; Dipyridamole; Chromosome Aberrations; chromozomální aberace; myši; dipyridamol; Gamma Rays; radioprotektivní látky; Animals